A large bioassay identifies Stb resistance genes that provide broad resistance against Septoria tritici blotch disease in the UK - Tidd, Henry; Rudd, Jason J.; Ray, Rumiana V.; Bryant, Ruth; Kanyuka, Kostya (Frontiers in Plant Science, 2023)
Septoria tritici blotch (STB) is one of the most damaging fungal diseases of wheat in Europe, largely due to the paucity of effective resistance genes against it in breeding materials. Currently dominant protection methods against this disease, e.g. fungicides and the disease resistance genes already deployed, are losing their effectiveness. Therefore, it is vital that other available disease resistance sources are identified, understood and deployed in a manner that maximises their effectiveness and durability. In this study, we assessed wheat genotypes containing nineteen known major STB resistance genes (Stb1 through to Stb19) or combinations thereof against a broad panel of 93 UK Zymoseptoria tritici isolates. Four infection symptom components (days post infection to the development of first symptoms and pycnidia, percentage coverage of the infected leaf area with chlorosis/necrosis and percentage coverage of the infected leaf area with pycnidia) were measured and average disease levels calculated for each genotype. The different Stb genes were found to vary greatly in the levels of protection they provided, with no Z. tritici isolate found to be virulent against all tested resistance genes. Disease resistance controlled by different Stb genes was associated with different levels of chlorosis, with high levels of early chlorosis in some genotypes correlated with high resistance to fungal pycnidia development. Stb10, Stb11, Stb12, Stb16q, Stb17, and Stb19 were identified as contributing broad spectrum disease resistance, and synthetic hexaploid wheat lines were identified as particularly promising sources of broadly effective STB resistances. Wheat genotypes carrying multiple Stb genes were found to provide higher levels of resistance than expected given their historical levels of use. The knowledge obtained here will aid UK breeders in prioritising Stb genes for future breeding programmes. In addition, this study identified the most interesting Stb genes for cloning and detailed functional analysis.